Проблемні питання діагностики та моніторингу вроджених вад серця у новонароджених - Сенаторова, Г.С.; Гончарь, М.О.; Бойченко, А.Д.; Кондратова, І.Ю.; Страшок, О.І.; Сенаторова; Тесленко, Т.О. (Таврический медико-биологический вестник, 2013)
В статье освещены и проанализированы основные проблемные вопросы диагностики и мониторинга врожденных пороков сердца у новорожденных с учетом данных современной литературы и на основании клинического опыта авторов; обсуждается тактика ведения пациентов в условиях родовспомагательніх учреждений. The problem of early diagnostics followed by timely surgery is of great importance due to high mortality rates accompanying natural current of congenital heart disease (CHD). The survival of infants with CHD depends on complexity of cardiovascular abnormality, presence of associated extracardiac malformations, and patient’s age by the time of establishing the diagnosis of CHD. Prenatal echocardiography have influenced significantly the possibilities and efficacy of treatment strategies in most cases of CHD, including critical ones. According to fetal echocardiographical studies, CHD are revealed in 0,4% of pregnant women of high risk.